Review of Petros Pizanias (ed), The Greek Revolution of 1821: A European Event - Amorati, Vasiliki (Historein, 2013)
The text is a book review of Petros Pizanias’ edited volume The Greek Revolution of 1821: A European Event, Istanbul: The Isis Press, 2011